2022
DOI: 10.3390/ijerph19095737
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Acceptance among Social Media Users: A Content Analysis, Multi-Continent Study

Abstract: Vaccine hesitancy is defined as a delayed in acceptance or refusal of vaccines despite availability of vaccination services. This multinational study examined user interaction with social media about COVID-19 vaccination. The study analyzed social media comments in 24 countries from five continents. In total, 5856 responses were analyzed; 83.5% of comments were from Facebook, while 16.5% were from Twitter. In Facebook, the overall vaccine acceptance was 40.3%; the lowest acceptance rates were evident in Jordan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…In the general population, the prevalence of vaccine acceptance was 43.0% (95% CI: 35.0–50.0%), among healthcare professionals it was 63.0% (95% CI: 42.0–70.0%), and among lesbian, gay, bisexual, and transgender (LGBTI) people, it was 84.0% (95% CI: 83.0–86.0%) [ 34 ]. In fact, people’s perceptions regarding vaccination acceptance may be influenced by a variety of local, racial, religious, cultural, and other factors, as well as false information, as was evidently seen during the COVID-19 pandemic [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the general population, the prevalence of vaccine acceptance was 43.0% (95% CI: 35.0–50.0%), among healthcare professionals it was 63.0% (95% CI: 42.0–70.0%), and among lesbian, gay, bisexual, and transgender (LGBTI) people, it was 84.0% (95% CI: 83.0–86.0%) [ 34 ]. In fact, people’s perceptions regarding vaccination acceptance may be influenced by a variety of local, racial, religious, cultural, and other factors, as well as false information, as was evidently seen during the COVID-19 pandemic [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, like with coronavirus disease (COVID-19), in order to achieve adequate vaccination coverage, people’s vaccine hesitancy (VH) to accept the vaccine is an important factor that vaccination programs should address. Fear of vaccine adverse effects, concerns regarding vaccine safety, efficacy, and effectiveness, lack of information, short duration of clinical trials, and social trust were the primary factors identified as influencing population attitudes regarding vaccination [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…VH was described by the Strategic Advisory Group of Experts on immunization (SAGE) as the delay in acceptance or rejection of vaccines even though the availability of vaccines is maintained [ 8 ]. The decision to get vaccinated is impacted by various factors such as risk perceptions, general attitudes toward vaccination, social and cultural barriers, complacency, convenience, and confidence or trust in the healthcare system [ 8 , 9 ]. A primary challenge faced by governments during the current COVID-19 pandemic is to address and develop the trust of populations to reach the maximum number of vaccinations and subsequent herd immunity [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the outbreak of the COVID-19 pandemic, great efforts have been devoted to studying the potential of social media in understanding the public's hesitancy in the fast developed vaccines [10,39,2,36], based on the pre-pandemic success in studying public opinions [34,23,27,30]. For instance, Cascini et al [10] reviewed the literature during the COVID-19 pandemic about how diffused information on social media impacts vaccination attitudes.…”
Section: Related Workmentioning
confidence: 99%
“…The second category leverages tools such as stance detection to infer various features of online activities from social media data of various formats including hashtags, hyperlinks and textual posts. For instance, Shaaban et al [36] studied vaccine acceptance with positions and tones of comments on various social media platforms. Lyu et al [25] inferred user demographics as well as vaccine attitudes through a text-based machine learning approach, and analysed vaccine acceptance among people with different demographic characteristics.…”
Section: Related Workmentioning
confidence: 99%